1998
DOI: 10.1099/00221287-144-10-2895
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Cornamonas testosteroni TAM1 to utilize phenol: organization and regulation of the genes involved in phenol degradatio

Abstract: Comamonas testosteroni TAU1 was not able to grow on phenol as a sole carbon and energy source, but it gained the ability to utilize phenol after a 2-3-week incubation in a medium containing phenol. Phenol hydroxylase (PH) and catechol2,3-dioxygenase (C230) were highly induced by phenol in the adapted strain designated as strain P1, suggesting that phenol was degraded via the meta-pathway. Gene clusters for phenol degradation were isolated from both strains TAU1 and P1. The structural genes encoding multicompon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 32 publications
0
68
0
1
Order By: Relevance
“…This yellow colour suggests that TA441 degrades testosterone via a meta-cleavage reaction. Our preliminary experiments showed that TA441 had a metacleavage enzyme which is produced when TA441 is grown on testosterone, in addition to the meta-cleavage enzymes already characterized in this strain (aphB and mhpB) (Arai et al, 1998(Arai et al, , 1999, and that the aphBmhpB -double knock-out mutant of TA441 still retained the ability to utilize testosterone as the sole carbon source. From these results, we considered that a metacleavage enzyme different from AphB and MhpB was involved in testosterone degradation in TA441, and we proceeded to partially purify the protein and determine the N-terminal sequence of the enzyme, as described in Methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This yellow colour suggests that TA441 degrades testosterone via a meta-cleavage reaction. Our preliminary experiments showed that TA441 had a metacleavage enzyme which is produced when TA441 is grown on testosterone, in addition to the meta-cleavage enzymes already characterized in this strain (aphB and mhpB) (Arai et al, 1998(Arai et al, , 1999, and that the aphBmhpB -double knock-out mutant of TA441 still retained the ability to utilize testosterone as the sole carbon source. From these results, we considered that a metacleavage enzyme different from AphB and MhpB was involved in testosterone degradation in TA441, and we proceeded to partially purify the protein and determine the N-terminal sequence of the enzyme, as described in Methods.…”
Section: Resultsmentioning
confidence: 99%
“…The tesB gene in pCP311 was disrupted by insertion of a SmaI fragment from pSKKm r , containing the Km-resistance gene, into the EcoRV site in tesB. The resultant plasmid, pTesB-Km r , which encodes the Km-resistance gene in the same transcriptional direction as tesB, was used for inactivation of the tesB gene in TA441 by homologous recombination according to the method described previously (Arai et al, 1998). A Km-resistant and carbenicillin-sensitive TA441 mutant was selected and designated strain TesB − .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aph, Arai et al, 1998Arai et al, , 2000Atd, Takeo et al, 1998;Cdo, Parales et al, 1997 and Data base accession no. AF 190463;Dmp, Singler et al, 1992;Nah, Bosch et al, 2000;Xyl, Harayama and Rekik, 1990;CbzX, Mars et al, 1999;AAG04733, probable P. aeruginosa SCD, Stover et al, 2000. FED, plant-type ferredoxin; SCD, short-chain dehydrogenase.…”
mentioning
confidence: 99%